Genealogia: da emergência às potencialidades contemporâneas - Santos, Cíntia Helena dos [UNESP]; Peres, Wiliam Siqueira [UNESP]; Toledo, Lívia Gonsalves [UNESP] (My University, 2010)
The article intends to articulate how the methodological proposal of Foucault, denominated genealogy, is applied to the field in which it emerged, considering that the proposal of this method appeared with the author’s study about the subject of the prisons. To apprehend the execution of the feathers in the contemporary epoch, we searched in Foucault’s theories the concepts of subjectivation processes, power relationships, discursive formations and dispositive. Starting from these concepts, we focused some practices and/or discursive formations of punishment and surveillance that happen at the present time to exemplify the form as the genealogical process raise an interlacement of subjects, information, appearances and disappearances that always obey to a normative logic. To unmask and to understand this logic can favor the liberation of manners of subjectivations crystallized in the punished people and in those ones that execute the punishment. Stiller, we question ourselves on which is the real function of the confinement, of the controls and, why not, if the paradigm of the modernity, the prison, had fail.

O artigo pretende articular como a proposta metodológica de Foucault denominada genealogia se aplica ao campo no qual ela emergiu, considerando que a proposta desse método surge com o debruçar do autor sobre a questão das prisões. Para apreender a execução das penas, na contemporaneidade, buscamos em Foucault os conceitos de processos de subjetivação, relações de poder, formações discursivas e dispositivos. A partir desses conceitos, focamos algumas práticas e/ou formações discursivas da punição e vigilância que ocorrem na atualidade, para exemplificar a forma como o processo genealógico suscita um entrelaçamento de questões, informações, surgimentos e desaparecimentos que obedecem sempre a uma lógica normativa. Desvendar e compreender essa lógica pode favorecer a libertação de modos de subjetivação cristalizados tanto entre os punidos quanto entre aqueles que executam a punição. Mais ainda, permite nos questionarmos sobre qual a real função do confinamento, dos controles e, por que não, se o paradigma da modernidade, a prisão, faliu.
Genealogy: from the emergency to the contemporary potentialities
Keywords: Genealogia; Execução de pena; Contemporaneidade; Poder; Genealogy; Feather execution; Contemporary epoch; Power